The Execution of Fiduciary Guarantees After Constitutional Court Decision No.2/PUU-XIX/2021 - Lathifah Hanim; Munsharif Abdul Chalim; MS. Noorman (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2023)
The Constitutional Court stated that the Irah-irah for the sake of justice based on belief in the One and Only God does not automatically have executive power. The research objective is to analyze the Execution of Fiduciary Guarantees Post Constitutional Court Decision No.2/PUU-XIX/2021 and analyze the obstacles and solutions in implementing the Execution of Fiduciary Guarantees Post Constitutional Court Decision No.2/PUU-XIX/2021. The research method is empirical juridical, supported by primary data and secondary data, with data collection techniques in the form of literature and interviews. Execution of Fiduciary Guarantees Post Constitutional Court Decision No.2/PUU-XIX/2021, namely that creditors cannot carry out forced executions themselves, for example by asking for assistance from the police, if there is a breach of contract (default) by the fiduciary right giver (debtor) against the creditor which are still not recognized by the debtor and the debtor objects to voluntarily handing over objects that are the object of the fiduciary agreement. The Court has reaffirmed in the Constitutional Court Decision Number 2/PUU-XIX/2021 that creditors must submit a request for execution to the District Court. and analyzing the obstacles and solutions in implementing the Execution of Fiduciary Guarantees after the Constitutional Court Decision No.2/PUU-XIX/2021. that is, many consumers do not understand that when they enter into a leasing agreement, they will only lease, they are actually renting their vehicle, they have to pay the rent every month, so when they are in arrears, even if they only have three months left, their vehicle must be taken by the creditor. This is an unfair regulation for consumers. On the one hand, the consumer has paid the specified down payment, on the other hand, the vehicle can be picked up at any time, regardless of how many months the remaining arrears are. There are deficiencies in Article 15 paragraphs (2) and (3) of the Fiduciary Guarantee Law which do not explain the procedure for executing the Fiduciary Guarantee Certificate, and do not regulate the mechanism for determining